EFEKTIVITAS INTERVENSI LATIHAN RANGE OF MOTION PADA ANAK DENGAN SPACE OCCUPYING LESION YANG MENGALAMI HEMIPARESIS: STUDI KASUS - Neng Heni Nurhaeni; Hendrawati, Sri; Mardhiyah, Ai (Jurnal Kesehatan An-Nuur, 2024)
Hemiparesis is a condition of weakness on one side of the body or the inability to move a limb on one side caused by stroke, head trauma, cerebral palsy and brain tumors. Weakness is a loss of muscle strength that can significantly reduce the ability to carry out daily activities. Hemiparesis, if not treated immediately, can cause permanent disability. One intervention that can be used to prevent muscle stiffness and increase muscle strength is Range of Motion (ROM) training. This study aims to evaluate the effectiveness of providing ROM intervention in cases of Space Occupying Lesion in children who experience hemiparesis. The method used is a case study design with a five process approach to nursing care starting from assessment, diagnosis, intervention planning, implementation and evaluation. The location of the case study was carried out in the Kemuning Room at RSUP Dr. Hasan Sadikin Bandung. The case obtained was an 11 year old girl being treated in the Kemuning Room at RSUP Dr. Hasan Sadikin Bandung since October 19 2020. The interventions provided are active ROM exercises on extremities that do not experience hemiparesis and passive ROM exercises on extremities that experience hemiparesis, for five days starting 26 October 2023 - 31 October 2023 with a duration of 20-25 minutes in the morning and afternoon. The results of the study showed that there was a significant increase in muscle strength on the third day of intervention, namely that the lower extremities experienced an increase, whereas before the intervention, 2/5 of the patient's muscle strength had movement but could not withstand gravity, up to 3/5, that is, there is movement with a full range of motion and is able to fight. gravity, and on the fourth and fifth days there was an increase in upper extremity muscle strength, namely from 2/5 to 3/5. In conclusion, ROM exercise intervention is effective and can be applied to children who experience hemiparesis.